2018
DOI: 10.1016/j.jcrs.2018.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Submicron loteprednol etabonate ophthalmic gel 0.38% for the treatment of inflammation and pain after cataract surgery

Abstract: In this study, submicron loteprednol etabonate gel 0.38% appeared safe and effective in the treatment of postoperative inflammation and pain whether instilled 2 times or 3 times a day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…The clinical development program designed to evaluate the safety and efficacy of LE (submicron) gel 0.38% included two similarly designed, Phase III, randomized, vehicle-controlled trials20,21 of LE gel 0.38% or vehicle instilled either BID or TID, for the treatment of postoperative inflammation and pain following cataract surgery with intraocular lens implantation. In both studies, LE gel 0.38% administered TID was safe and effective in the treatment of ocular inflammation and pain following cataract surgery, leading to the United States FDA approval of this new LE (submicron) gel formulation with TID dosing in February 2019 with the brand name of Lotemax ® SM 18.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical development program designed to evaluate the safety and efficacy of LE (submicron) gel 0.38% included two similarly designed, Phase III, randomized, vehicle-controlled trials20,21 of LE gel 0.38% or vehicle instilled either BID or TID, for the treatment of postoperative inflammation and pain following cataract surgery with intraocular lens implantation. In both studies, LE gel 0.38% administered TID was safe and effective in the treatment of ocular inflammation and pain following cataract surgery, leading to the United States FDA approval of this new LE (submicron) gel formulation with TID dosing in February 2019 with the brand name of Lotemax ® SM 18.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 2 pivotal Phase 3, randomized, multicenter, vehicle-controlled clinical trials have demonstrated that LE (submicron) gel 0.38% appeared safe and effective for the reduction of inflammation and pain postcataract surgery, with a TID dosing regimen. 47,54 In both studies, the numbers of subjects with complete resolution of ocular pain and anterior chamber cells (primary efficacy endpoint) were significantly higher in the LE (submicron) gel 0.38% TID dosing group compared to the vehicle group. Improvements in resolution of inflammation and pain postcataract surgery were also observed with BID dosing, despite the drug not meeting the primary efficacy endpoint in 1 study.…”
Section: Discussionmentioning
confidence: 98%
“…In support of the latter, there were no reports of drug-related blurred vision, and most subjects reported no discomfort upon instillation in a Phase 3 study evaluating LE gel 0.38% for treatment of postsurgical inflammation and pain. 47…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations